Dietary diversity among smallholder households in Bukoba district, Tanzania and Kiboga district, Uganda - Nabuuma, D.; Ekesa, B.; Kennedy, G. (African Journal of Food, Agriculture, Nutrition and Development, 2018)
Undernutrition in developing countries continues to affect 780 million people resulting in poor growth and development; increasing the burden of disease and imposing a number of costs on the affected countries. The aim of this study was to establish the dietary diversity and consumption patterns among small-holder farming households. A cross-sectional study was carried out in Kiboga district, Uganda and Bukoba district, Tanzania with 220 and 199 households, respectively. Results from the 24 hour recall showed that white roots, tubers and bananas were the most consumed food group in the two districts with a significantly higher consumption in Kiboga than Bukoba. However, households in Bukoba had higher dietary diversity scores compared to those in Kiboga even though both districts had 52% of the households consuming diets with moderate dietary diversity. The percentage of households consuming vitamin A rich vegetables and fruits, and animal protein (flesh meats, organ meats and eggs) was negligible. There was no significant difference between food group consumption at household level and that of the youngest 6-59 month-old child within these households. High consumption of a food group and absence of a food group by the whole household was matched by the consumption of the children. Only 48% and 35% of caregivers in Kiboga and Bukoba, respectively reported preparing special meals for the child. Younger caregivers, ability of households to rent out land, and distance to market were variables that significantly influenced intake of vitamin A and iron but not protein. The results highlight opportunities for the promotion of vitamin A- rich fruits and vegetables, and protein foods in between the main household meals of the day, as well as avenues through which nutrition education can be reinforced to improve the knowledge and skills of the households, especially the decision makers and care givers of children under five years of age.